2020
DOI: 10.1101/2020.11.26.400234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Orthogonal targeting of KDM6A/B and HDACs mediates potent therapeutic effects in IDH1-mutant glioma

Abstract: IDH1/2-mutant gliomas are primary brain tumors for which curative treatments are lacking. Using a chemical screen targeting chromatin modifiers, we identified the histone H3 K27me3 demethylase inhibitor GSK-J4 and class I histone deacetylase inhibitors such as Belinostat as potent, genotype-selective agents against IDH1-mutant glioma. RNA-sequencing on paired wild-type and IDH1R132H cells revealed induction of stress-related pathways in IDH1R132H cells, which was dependent on the onco-metabolite 2-hydroxygluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…It was even reported that long-term treatment with mutant IDH inhibitors accelerated cell growth and shortened the in vivo survival [45]. Moreover, some studies suggested that mutant IDH inhibitors may interfere with therapeutic approaches targeting mutant IDHcaused vulnerabilities [36]. Therefore, even though mutant IDH enzymes create favorable conditions for tumorigenesis and selection of aggressive mutations, their inhibition may not always be effective in a tumor that has completed its stages of development.…”
Section: Mutant Idh Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was even reported that long-term treatment with mutant IDH inhibitors accelerated cell growth and shortened the in vivo survival [45]. Moreover, some studies suggested that mutant IDH inhibitors may interfere with therapeutic approaches targeting mutant IDHcaused vulnerabilities [36]. Therefore, even though mutant IDH enzymes create favorable conditions for tumorigenesis and selection of aggressive mutations, their inhibition may not always be effective in a tumor that has completed its stages of development.…”
Section: Mutant Idh Inhibitorsmentioning
confidence: 99%
“…Prolonged presence of mutant IDH1 renders most of these modifications irreversible, which may have critical importance for tumor progression. Based on this epigenetic reprogramming, we recently conducted chemical screening in IDH1-mutant GBM cells, including inhibitors of epigenetic enzymes [36]. We found that IDH1-mutant GBM cells are sensitive to different epigenetic enzyme inhibitors such as DNMT inhibitor 5-azacitidine, HMT inhibitor chaetocin, KDM inhibitor GSK-J4, and HDAC inhibitor belinostat.…”
Section: Combination Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up studies have been encouraging but mixed [25][26][27][28][29][30] . Interestingly three recent studies found that HDAC inhibitors may be speci cally effective in IDH1 mutant gliomas [31][32][33] . Histone deacetylases are ubiquitously expressed in various cell types and regulate multiple cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, acetylation of histones leads to relaxed chromatin allowing aberrant gene expression whereas methylated histones are often associated with gene silencing [9,10]. Recent cancer genome sequencing studies revealed mutations in many epigenetic modifiers that are associated with various cancers [11], such as DNMT3A in acute myeloid leukemia [9,12], IDH1/2 in glioblastoma [13,14], CREBBP/EP300 in small-cell lung cancer [15] and ARID1A in gastric cancer [16]. These driver mutations are thought to act in part by increasing cellular plasticity during development of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%